A Retrospective Analysis of Rates of Malingering in a Forensic Psychiatry Practice - Svete, Lillian J.; Tindell, William W.; McLouth, Christopher J.; Allen, Timothy S. (Journal of the American Academy of Psychiatry and the Law Online, 2025)
Malingering is defined as the intentional falsification or exaggeration of symptoms for secondary gain. The prevalence of malingering varies widely among different medicolegal contexts, emphasizing the need to identify additional predictive factors when considering the diagnosis. This study measured rates of malingering in a sample of 1,300 subjects from a forensic psychiatry practice located in Lexington, Kentucky. Among those who failed at least three symptom or performance validity scales, odds ratios for malingering were approximately twice as high in subjects with less than a college education (p = .011), those referred by the opposing counsel (p = .001), and those meeting criteria for a mental illness in three or more DSM-5 diagnostic categories (p = .015). Those evaluated for worker’s compensation and head injury were more likely to malinger than other case types (p = .028). Men were found to malinger at a higher rate than women (p = .014), and no significant differences were observed based on race. These results indicate that education, gender, psychiatric history, case type, and referral type may be important factors to consider when assessing for malingering.